2020
DOI: 10.9734/jamb/2020/v20i330230
|View full text |Cite
|
Sign up to set email alerts
|

PCR and Sequencing Base Detection of Gummosis Disease on Citrus aurantifolia Caused by Lasiodiplodia theobromae and Evaluation of Its Antagonisms

Abstract: Diplodia gummosis disease caused by Lasiodiplodia theobromae is an economically important postharvest fruit decay that occurs on all types of citrus grown in Bangladesh. The present investigation was conducted to isolate and identify the pathogenic fungus responsible for postharvest diplodia gummosis disease (DGD) of citrus as well as the evaluation of its biological control through microbial antagonists. DGD causing pathogen was identified by physiological, morphological and molecular methods. The pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
1
8
0
1
Order By: Relevance
“…Huda-Shakirah et al (2020) reported 99.53% similarity with Fusarium concentricum isolated from Hibiscus sabdariffa. The results of PCR and ITS sequencing confirm the isolated fungus as F. concentricum, which is supported by some other researcher's findings (Chowdhury et al, 2019;Hasan et al, 2020;Hyun et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Huda-Shakirah et al (2020) reported 99.53% similarity with Fusarium concentricum isolated from Hibiscus sabdariffa. The results of PCR and ITS sequencing confirm the isolated fungus as F. concentricum, which is supported by some other researcher's findings (Chowdhury et al, 2019;Hasan et al, 2020;Hyun et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…The main objective of the present study was to study biological control measures for this fungus. Plant extracts are now a superior choice to control different plant pathogens, as reported by several previous studies (Hasan et al, 2020;Kareem & Al-Araji, 2017;Parveen et al, 2014). In our study, we found that the plant extracts Allium sativum, Zingiber officinale, and Coccinia grandis have significant inhibitory effects on mycelial growth of Fusarium species.…”
Section: Discussionmentioning
confidence: 80%
“…was previously isolated and identified (Accession No. MT856371) from postharvest Citrus reticulata fruit rot (Hasan et al, 2020). The culture was preserved at the Department of Genetic Engineering and Biotechnology, University of Rajshahi (Rajshahi, Bangladesh).…”
Section: Collection Of Fusarium Spmentioning
confidence: 99%
“…They recorded optimum pH 5.5-6.5 for the growth of this fungus, which indicates that slightly acidic to neutral pH is optimum for its growth. L. theobromae has a wide host range, such as banana [42], mango [34], guava [43], coconut [16], citrus [44], papaya [45], jackfruit [46], and so forth in which it causes severe diseases. In our study, we found that both the isolates of L. theobromae showed pathogenicity toward fruits of dragon fruit, banana, mango, and guava.…”
Section: Discussionmentioning
confidence: 99%